Religious participation versus shopping: What makes people happier? - Danny Cohen-Zada; William Sander (Institute for the Study of Labor (IZA), 2010)
In this paper, we first explore how an exogenous increase in the opportunity cost of religious participation affects individuals' religious participation and reported happiness using data from the General Social Survey. The exogenous shift in the cost of religious participation is a result of repealing of so-called blue laws which restrict retail activity on Sundays. We find that repealing blue laws causes a significant decline in the level of religious participation of white women and in their happiness. We do not observe any significant decline in reported happiness of other groups whose religious participation was not significantly affected by repeal. We also use repeal as an instrumental variable (IV) for church attendance and provide direct evidence that church attendance has a significant positive effect on happiness, especially for women.
Keywords: K10; J16; 330; religious participation; happiness; blue laws; Religionsgemeinschaft; Mitgliedschaft; Opportunitätskosten; Zufriedenheit; USA